Modeling of flexural-dominated composite shear walls - Ghani, Muqtadir; Pennung Warnitchai; Anwar, Naveed; Thanakorn Pheeraphan; Raktipong Sahamitmongkol; Computer and Structures Inc. (CSI), USA; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Composite Shear Wall is being used across the world to achieve better performing shear walls compared to the conventional Reinforced concrete shear wall. With the advancements of new types of composite shear walls, the application into industry involves generation of modeling technique able to predict the behavior of the wall. An experiment of steel encased composite shear wall was set as a basis for modeling of composite shear wall. Three types of modeling techniques were generated for modeling of composite shear wall on SAP2000 i.e. Layered shell element with shell boundary element, layered shell element with line boundary element and a single column approach. The modeling is done in two phases and with each modeling phase, the methodology is generated to apply the modelling technique on composite shear walls. The first phase focuses on the general behavior of the composite shear wall whereas the second phase focuses on each individual methodology under study. The global and local behavior of the wall is studied for each of the composite shear wall modeling technique. Being able to predict the global and local behavior to an extent, the Layered shell element with shell boundary element was suggested for local behavior and Layered shell element with line boundary element for global behavior whereas the single column approach managed to predict till peak strength.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Composite materials; Shear walls -- Materials -- Testing; SAP2000 (Computer program)